Genetic variability among Commelina weed species from the states of Paraná and São Paulo, Brazil - Rocha, D. C. (2009)
This work aims to carry out a comparative analysis using RAPD molecular markers in four Commelina weed species from the state of Paraná and C. benghalensis populations from the states of Paraná and São Paulo, Brazil. The genomic plant DNA sample was extracted from the leaves, separated, randomly fragmented and amplified by PCR. Random amplified polymorphic DNA fragments (RAPD markers) were analyzed by using POPGENE statistical program. Eighty-five primer sequences were tested but only three were suitable as molecular markers producing 37 DNA polymorphic fragments for comparisons among four Commelina species and 22 polymorphic fragments for comparisons among C. benghalensis populations. The results showed that there were inter-specific and intra-specific genetic variabilities among Commelina plant genera. Genetic diversity analysis between species indicated four mono-specific clusters and it was suggested to keep C. villosa as one species. Regarding the intra-specific genetic variability of C. benghalensis alone, three groups were verified, although there were 13 populations from two geographical areas. However, these clusters do not correspond to the distinct characteristics verified.